A microplate enzyme-immunoassay for toxoplasma antibody. - Voller, A (1976)
A new test for the detection and measurement of toxoplasma antibody is described. Test sera are reacted with antigen-sensitized wells in micro-haemagglutination plates. Any attached antibody is shown by the addition of an enzyme-labelled antiglobulin followed by assay of the enzyme reaction with its substrate. The test is easy to carry out on a large scale, and there is a positive correlation between the results and dye test and haemagglutination test titres.